State, pluralism, and the Indian historical tradition - Chandra, Satish (Oxford : Oxford University Press, 2009)
This collection of seminal essays, by one of the most eminent historians and educationists, provides a comprehensive view of medieval India. It explores four main themes-evolution of state, role of towns and urbanism, the historical and maritime traditions, and cultural pluralism. Towards the end of the volume, Satish Chandra surveys the role of leading Indian historians in promoting a more critical and secular view of medieval India. In a concluding historical assessment of the last fifty years, he highlights the role India could play in a challenging world order. -- Publisher description.
Includes bibliographical references and index.
Keywords: Cultural pluralism -- India; Bhakti; Sufism -- India; India -- Politics and government; India -- Social conditions; India -- Economic conditions